Método para avaliação das condições ergonômicas em serviços da construção civil - Martins, Andreia Sofia Moreira (Universidade Federal de São Carlos, 2021)
The labor activity in the civil construction sector is among the most harmful for workers and the activities produced require a high repetitiveness of movements and handling of heavy materials and components, which make it difficult to use correct standards of posture and contribute to the high rate of musculoskeletal injuries. This study aimed to present a method to assess working conditions and improve the analysis of the risks that the worker is exposed to from the ergonomics point of view. The method was developed through the articulation of different tools, such as the Ergonomic Work Analysis (AET) methodology and the application of other ergonomic risk assessment tools, such as the Ergonomic Workplace Analysis (EWA), Ovako Working Posture Analysing System (OWAS), Rapid Entire Body Assessment (REBA) and Metabolic Equivalent (MET). The research was divided into three phases. In the first phase, a bibliographic review was carried out on ergonomics in civil construction and two exploratory Case Studies were carried out in the execution of the masonry service, one for sealing and the other structural, which included: visits to construction sites; interviews with those responsible and the masonry workers; photographs and footage of the execution of the works; and the application of AET and the EWA tool. For the second phase, six Case Studies were carried out and the application of the AET and the EWA, OWAS, REBA and MET tools were carried out. The third phase presents the conception and validation of the method, developed through the diagnosis generated by the application of ergonomic risk assessment tools in the Case Studies. The diagnosis made it possible to identify the most harmful situations practiced during masonry activities and made it possible to present recommendations for the mitigation of risks in sealing and structural masonry services. Therefore, this study demonstrates that the articulation of different methods and tools improves the development of ergonomic analysis, in particular, the integrated identification of risk factors and risk assessment through the use of specific tools, essential for a diagnosis in situations in the construction industry.
Method for assessing ergonomic conditions in construction services
Keywords: Construção Civil; Análise ergonômica; Alvenaria; Construction; Ergonomic analysis; Masonry; EWA; OWAS; REBA; MET; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL